Pengaruh Pornografi Di Media Sosial Terhadap Remaja Di Desa Simatahari Kecamatan Kotapinang Kabupaten Labuhanbatu Selatan - Pardamean, Syahron; Rasyid, Abdul; Monang, Sori (Universitas Labuhanbatu, 2023)
This study aims to find out how pornography on social media influences adolescents in Simatahari Village. To achieve the intended purpose, this research uses qualitative research with descriptive analysis methods. Data collection techniques were carried out by observation, interviews and documentation studies. The results of this study: (1) The significant effect of pornography felt by adolescents is loss of concentration or failure to focus on work and learning. (2) Backgrounds that influence adolescent access to pornography are divided into three types, namely, lack of knowledge about sex, lack of parental approach and exposure to videos with pornographic content on social media. (3) The solution given is to invite teenagers to take part in activities carried out by the Simatahari Village Mosque Prosperity Agency and watch a number of tausiyah videos from YouTube.